2023
DOI: 10.3233/jpd-223565
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Sleep Electroencephalogram in Parkinson’s Disease: A Case-Control Study

Abstract: Background: Sleep disorders are common in Parkinson’s disease (PD) and include alterations in sleep-related EEG oscillations. Objective: This case-control study tested the hypothesis that patients with PD would have a lower density of Scalp-Slow Wave (SW) oscillations and higher slow-to-fast frequencies ratio in rapid eye movement (REM) sleep than non-PD controls. Other sleep-related quantitative EEG (qEEG) features were also examined, including SW morphology, sleep spindles, and Scalp-SW spindle phase-amplitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…SW and spindle phase-amplitude coupling (PAC) promotes memory consolidation, and declines with physiological aging (Helfrich et al, 2018;Muehlroth et al, 2019). In the only prior study investigating SW-spindle PAC in PD, we found higher non-uniformity in SW-spindle coupling in PD patients compared to controls (Memon et al, 2023).…”
Section: Introductioncontrasting
confidence: 49%
See 3 more Smart Citations
“…SW and spindle phase-amplitude coupling (PAC) promotes memory consolidation, and declines with physiological aging (Helfrich et al, 2018;Muehlroth et al, 2019). In the only prior study investigating SW-spindle PAC in PD, we found higher non-uniformity in SW-spindle coupling in PD patients compared to controls (Memon et al, 2023).…”
Section: Introductioncontrasting
confidence: 49%
“…To detect slow waves (SW) and sleep spindles, EEG data without artifacts were processed using a custom MATLAB script that utilized validated algorithms previously employed in studies involving older adults ( Mölle et al, 2011 ; Staresina et al, 2015 ; Helfrich et al, 2018 ; Memon et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations